P179 Characteristics of MSM attendees and rate of STI re-testing in a dedicated MSM service versus the general walk in GU clinic. (30th June 2016) - Proserpio, Mauro; Dosekun, Olamide
Abstract : Background: Men who have sex with men (MSM) in London experience inequalities in sexual health despite bearing the highest burden of sexually transmitted infections (STIs). Annual STI screening in MSM is recommended in the UK. Our London based clinic has a dedicated service for MSM to foster rapport with patients, promote safer sex and normalise regular STI screening. Aims: To describe characteristics of MSM attending a general walk in clinic (GWI) versus a dedicated MSM service (MSMS), and rate of STI retesting between the two clinics. Methods: A case-note review of MSM and bisexual male attendees between October and December 2014 in the GWI and MSMS and new episode attendances up to January 2016. Results: Information on 101 MSM (50 GWI, 51 MSMS) was collected; median age was 32 (range 25–59) and 29 (22–49) years respectively, and they were of white ethnicity in 33/50, 66%, and 40/51, 78% in GWI and MSMS respectively. There were no differences in HIV status or new STI/HIV diagnoses between clinic attendees. There were 82 and 104 further new episode attendances amongst these GWI and MSMS attendees respectively; the latter mostly re-attended the MSMS (69/101, 68%). There was no differences in number of non-reattenders (18, 36%; 19, 37% respectively). Conclusion: Patients in our MSMS tended to re-attend more for repeat screening and within the same service, in comparison to GWI. Similar numbers of patients never re-attended in both clinics, suggesting that further strategies are needed to embed a culture of regular screening in this group.